Response of Wheat to Residual Fertilizer Nitrogen Applied to Previously Failed Corn - D. W. Sweeney; D. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2015)
When drought conditions result in poor corn growth and yield, the potential exists for carryover of fertilizer nitrogen (N) to wheat. Soil sampling at the wheat jointing stage showed that NO3-N levels increased slightly as previous N rate increased up to 240 lb/a N, but did not appear sufficient for the wheat yield increase to previous N rate. The relationship between wheat normalized difference vegetative index (NDVI) measurements at jointing and wheat yield was linear. The use of crop active sensors such as the GreenSeeker (Trimble Navigation Ltd., Sunnyvale, CA) may provide plant response data to supplement soil sampling to more adequately determine residual effects on a following wheat crop.
Keywords: residual nitrogen; wheat; drought; corn